Frontier transformations: development visions, spaces and processes in Northern Kenya and Southern Ethiopia - Mosley, J; Watson, E (Routledge, 2016)
African approaches to development have shifted, particularly in north-eastern Africa. Donor-driven policies have given way to state-led development ‘visions’, often with a focus on large-scale infrastructure projects – feeding into and reflecting ‘Africa Rising’ discourses. In Kenya and Ethiopia, these visions include flagship projects in the geographical frontiers, areas previously viewed as buffer zones, whose people have been historically marginalised. This paper adapts the analytical framework from James Scott’s Seeing Like a State in order to compare Kenya’s and Ethiopia’s state visions, and to understand the risks to the populations intended to benefit from such visions from the unintended (but predictable) consequences such projects have had in the past.